Does Patient Self-Awareness Predict Ankle Fractures? (Translation: The University of Toledo Journal of Medical Sciences, 2021)
Introduction: Ankle injuries represent one of the most common sports and extremity related complaints presented in emergency departments (ED) with over five million ankle injuries annually arising in the United States. The 2007 US National Health Statistics Report stated that lower limb and ankle complaints accounted for 4.1% of all reported body sites undergoing injury in the ED. The purpose of this study was to examine how frequently a sample of ED patients’ perception of having a possible ankle fracture was predictively associated with results of their X-ray evaluation results. Methods: After 2017 IRB approval, a sample of consented adult patients receiving care at the authors’ two Ohio and Michigan ED were asked, “Do you think you broke your ankle?” Regardless of each patient’s answer, they received an X-ray to evaluate for an ankle fracture that was interpreted by a radiologist. Results: A total of 69 eligible patients received an ankle X-ray. The total number of ankle fractures confirmed by X-ray was 20 (29.4% of sample) while 48 (70.5%) of ankles that were X-rayed were not fractured. Six (28.5%) out of 21 males and 14 (30.4%) out of 46 females were found to have a confirmed ankle fracture. The sensitivity of the perceived ankle fracture question was at or below 50% in all sample subgroups except for smokers at 67%. Conclusion: These findings support the importance of an ED clinician’s intuition when considering a patient’s own self-assessment during their clinical decision-making processes
Keywords: X-ray, emergency department, ankle, fracture, radiation, healthcare cost, pain scale, ambulation status, self-awareness